Distributed Space-Time Codes for Full-Duplex IR-UWB Amplify-and-Forward Cooperation - Abou-Rjeily, Chadi (IEEE transactions on wireless communications, 2015)
In this paper, we consider the problem of full-duplex (FD) relaying in the context of impulse-radio ultra-wideband (IR-UWB) communications. In particular, we propose two novel distributed space-time block codes (STBCs) suitable for the amplify-and-forward (AF) cooperation protocol with one and two relays. Despite the fact that FD relaying results in significant levels of interference between the transmit and receive antennas of each relay, it introduces new concepts to the problem of distributed STBC design. Compared to half-duplex (HD) STBC, FD-STBC is subject to an additional constraint that imposes the structure of the codewords while it offers the predominant advantage that resides in the possibility of including a smaller number of information symbols per codeword for achieving a full rate. We take advantage of this potential for constructing fully-diverse, full-rate and totally-real IR-UWB FD-STBCs that outperform the existing HD-STBCs for all practical levels of the residual self loop interference. In fact, for the sake of transmitting at full rate, the best known distributed HD-STBCs for the non-orthogonal AF protocol require the joint encoding/decoding of 4N_{r} symbols where N_{r} is the number of relays. On the other hand, the proposed FD-STBCs require embedding only N_{r} +2 symbols per codeword for transmitting at full rate. Following from this fact, not only the decoding complexity is reduced, but also the coding gains are improved resulting in enhanced performance levels.